DESIMINASI INFORMASI DAN EDUKASI MITIGASI CORONAVIRUS DISEASE – 2019 (COVID-19) DI SULAWESI TENGGARA - La Ode Alwi; La Ode Santiaji Bande; Teri Pakki; Saefuddin Saefuddin; Anas Nikoyan; Hartina Batoa (Jurnal Pengabdian NUSANTARA, 2023)
Some of the problems faced by the community as a result of the Coronavirus Disease – 2019 (COVID-19) have limited social access to the community in everyday life. By looking at these problems, there is a need for Services on Information Dissemination and Education on Mitigation of Coronavirus Disease – 2019 (COVID-19. The implementation of Community Service Program Lecturers Thematic Dissemination of Information and Education on Coronavirus-2019 (COVID-19) Mitigation, was carried out in several stages, namely: (i) socialization of the implementation of trials at the community level; (ii) carry out an understanding test about KKN on how to mitigate the Coronavirus-2019 (COVID-19); (ii) conducting training for the community on the use of local resources, such as coconut oil, ginger, saraba and moringa as COVID-19 mitigation materials. The results of the service show that: (i) the community is increasingly aware of the importance of mitigating COVID-19 and how to prevent COVID-19; (ii) the community knows the types of local resources that are easy to obtain and easy to make as medicine in the fight against COVID-19; (iii) the community is able to make and apply local resources (moringa, ginger and coconut oil) as a COVID-19 mitigation